Dopaminergic modulation of pain signals in the medial prefrontal cortex: Challenges and perspectives. (29th May 2019) - Huang, Shuo; Borgland, Stephanie L.; Zamponi, Gerald W.
Abstract: Chronic pain is a massive socieoeconomic burden and is often refractory to treatment. To devise novel therapeutic interventions, it is important to understand in detail the processing of pain signals in the brain. Recent studies have revealed shared features between the brain's reward and pain systems. Dopamine (DA) is a key neuromodulator in the mesocorticolimbic system that has been implicated not only in motivated behaviours, reinforcement learning and reward processing, but also in the pain axis. The medial prefrontal cortex (mPFC) is an important region for mediating executive functions including attention, judgement, and learning. Studies have revealed that the mPFC undergoes plasticity during the development of chronic pain. The mPFC receives dopaminergic input from the ventral tegmental area (VTA), and stimulation of these inputs has been shown to modulate the plasticity of the mPFC and anxiety and aversive behaviour. Here, we review the role of the mPFC and its dopaminergic modulation in chronic pain.